Unsteady MHD flow of a dusty nanofluid past a vertical stretching surface with non-uniform heat source/sink - C. Sulochana; J. Prakash; Sandeep N (Chemical Engineering Diponegoro University, 2016)
We analyzed the momentum and heat transfer characteristics of unsteady MHD flow of a dusty nanofluid over a vertical stretching surface in presence of volume fraction of dust and nano particles with non uniform heat source/sink. We considered two types of nanofluids namely Ag-water and Cu-water embedded with conducting dust particles. The governing equations are transformed in to nonlinear ordinary differential equations by using similarity transformation and solved numerically using Shooting technique. The effects of non-dimensional governing parameters on velocity and temperature profiles for fluid and dust phases are discussed and presented through graphs. Also, the skin friction coefficient and Nusselt number are discussed and presented for two dusty nanofluids separately in tabular form. Results indicate that an increase in the volume fraction of dust particles enhances the heat transfer in Cu-water nanofluid compared with Ag-water nanofluid and a raise in the volume fraction of nano particles shows uniform heat transfer in both Cu-water and Ag-water nanofluids.